2016
DOI: 10.4103/0972-5229.194006
|View full text |Cite
|
Sign up to set email alerts
|

Using the first drop of blood for monitoring blood glucose values in critically ill patients: An observational study

Abstract: Context:Using the first drop or second drop of blood while measuring blood glucose (BG) values.Objective:The study was planned to compare the BG values from the first and second drops of blood.Research Settings:The study was conducted at the Main Intensive Care Unit, PGIMER, Chandigarh, India.Research Design:This study was a comparative study.Materials and Methods:Ninety patients aged 2–93 years were enrolled in this study. BG values from the first and second drops of blood were taken and compared.Statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…At the same time, it was determined that the use of the first drop of blood in capillary measurements could save time, reduce pain, and save medical resources (Li et al, 2014). In the study by Saini et al (2016), it was determined that there was no statistically significant difference in the values of blood glucose between first and second drops of blood; any of the drops can be used for measuring of blood glucose level as the difference was not statistically significant. However, if hands were washed and to decrease the blood loss in the critically ill patients where the blood glucose levels were measured frequently, using the first drop of blood was advised (Saini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it was determined that the use of the first drop of blood in capillary measurements could save time, reduce pain, and save medical resources (Li et al, 2014). In the study by Saini et al (2016), it was determined that there was no statistically significant difference in the values of blood glucose between first and second drops of blood; any of the drops can be used for measuring of blood glucose level as the difference was not statistically significant. However, if hands were washed and to decrease the blood loss in the critically ill patients where the blood glucose levels were measured frequently, using the first drop of blood was advised (Saini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies that have shown no difference in the blood glucose concentration between the first and the second drops of blood released by a lancet. 23 The blood concentration of jet-released samples collected during the first 15 seconds for each participant was lower than of lancet-released samples. Some of this dilution is likely caused by the injectate, in addition to interstitial fluid.…”
Section: Discussionmentioning
confidence: 78%
“…This is consistent with other studies that have shown no difference in the blood glucose concentration between the first and the second drops of blood released by a lancet. 23…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was found that the fasting and fullness values of the first blood drop collected by wiping the finger with alcohol after washing hands could be used, because there was no significant difference between the first drop and second drop values. Likewise, Mehdizadeh Torghadar et al ( 2018), Li et al (2014), Palese et al (2016), andSaini et al (2016) also determined no statistically significant difference between first and second capillary blood drops and recommended the use of using the capillary first blood drop after washing hands in critical patients whose blood glucose levels are frequently measured for minimizing blood loss. Palese et al (2016) in Type 1 diabetes patients at emergency services and Li et al (2014) in patients self-measuring their own glucose levels found that there was no significant difference between values obtained from the first and second capillary blood drops of patients with high blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%